The pollution of the Adriatic Sea: scientific knowledge and policy actions. (4th August 2014) - Conti, M.E.
This paper presents an updated overview of the pollution of the Adriatic Sea, and especially on the phenomenon of eutrophication. The process of eutrophication can be defined as an increased availability of nutrients in the aquatic ecosystem with a consequent increase in the vegetable biomass. The situation is described from both a scientific and a socio–economic point of view. Particularly, the state of marine pollution along the Adriatic coast and the activity of national and local anti–pollution agencies are presented and discussed.